An International Debt Facility? (IMF Working Papers; Working Paper, 1988)
A common proposal designed to deal with the developing countries' debt problem is that there be set up some kind of 'international debt facility' which would buy up debt at a discount and then write down its contractual value, hence providing debt relief. There are three main parties to the proposed transaction, namely the debtor governments, the creditor banks, and the owners of the facility. The paper analyzes the central question of how each of the parties would be affected and, specifically, to what extent there would be some redistribution between them as a result of the arrangement.